2022
DOI: 10.7554/elife.72875
|View full text |Cite
|
Sign up to set email alerts
|

Minimal requirements for a neuron to coregulate many properties and the implications for ion channel correlations and robustness

Abstract: Neurons regulate their excitability by adjusting their ion channel levels. Degeneracy - achieving equivalent outcomes (excitability) using different solutions (channel combinations) - facilitates this regulation by enabling a disruptive change in one channel to be offset by compensatory changes in other channels. But neurons must co-regulate many properties. Pleiotropy - the impact of one channel on more than one property - complicates regulation because a compensatory ion channel change that restores one prop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 91 publications
4
41
0
Order By: Relevance
“…A homeostatic mechanism based on a single feedback signal (O’Leary et al ., 2013, 2014) that has been suggested to play a role in model robustness was not compatible with our model in our hands since it decreased ion channel degeneracy. This is in agreement with a recent study (Yang et al ., 2022) that provided new insights into the complex relationship between ion channel diversity and homeostatic co-regulation of ion channel densities. The study by Yang et al (2022) suggested the necessity of more than one master feedback regulator (i.e.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…A homeostatic mechanism based on a single feedback signal (O’Leary et al ., 2013, 2014) that has been suggested to play a role in model robustness was not compatible with our model in our hands since it decreased ion channel degeneracy. This is in agreement with a recent study (Yang et al ., 2022) that provided new insights into the complex relationship between ion channel diversity and homeostatic co-regulation of ion channel densities. The study by Yang et al (2022) suggested the necessity of more than one master feedback regulator (i.e.…”
Section: Discussionsupporting
confidence: 94%
“…This is in agreement with a recent study (Yang et al ., 2022) that provided new insights into the complex relationship between ion channel diversity and homeostatic co-regulation of ion channel densities. The study by Yang et al (2022) suggested the necessity of more than one master feedback regulator (i.e. more regulators than just global calcium) for homeostatic feedback loops, which must co-tune numerous degenerate and pleiotropic ion channels to achieve multiple regulated functions or objectives (cf.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Thus, homeostatic co-tuning of multiple tasks seems possible only with sufficiently large ion channel diversity (see also [36]). In addition, ion channel correlations seem to arise if the solution space (defined as a difference between the number of dimensions of parameter space and the number of dimensions of performance space) is low-dimensional [124]. It would be interesting to compare these predictions to experiments accompanied by simulations in biophysically and morphologically more complex models complemented by Pareto analysis.…”
Section: Open Questionsmentioning
confidence: 99%